THE EFFECT OF ACUPRESSURE THERAPY ON BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS FOR 0-6 MONTHS IN BANTARJAYA VILLAGE, PEBAYURAN DISTRICT, KABUPETEN, BEKASI IN 2023 - Neneng Julianti (NHM PRESS, 2023)
Nationally, the coverage of exclusive breastfeeding in Indonesia in 2020 is 66.1%, so that the achievement of exclusive breastfeeding in Indonesia has not reached the target. The results of a preliminary study have never applied Acupressure Therapy when providing obstetric to postpartum mothers. The purpose of this study was to determine the effect of acupressure therapy on breast milk production in breastfeeding mothers 0-6 months in Bantarjaya Village, Bekasi Regency in 2023. The research method uses quantitative methods (Quasi-Experiment), Wilcoxon's statistical test. The population and sample in this study were all breastfeeding mothers 0-6 months in Bantarjaya Village, which was 53 people, using the total sampling technique. Questionnaire instrument. Data analysis is a univariate, bivariate analysis. The results showed that there were breastfeeding mothers whose milk production increased a lot to 43 people (81.1%). Meanwhile, for breastfeeding mothers whose milk production is less / slightly reduced to 10 people (18.9%). The results of statistical tests are known to Asymp. Sig is 0.000 (P < 0.05), so it can be concluded that there is an effect of acupressure therapy with an increase in breast milk production in breastfeeding mothers 0-6 months in Bantarjaya Village, Pebayuran District, Bekasi Regency in 2023.